Quantum speed limit and optimal control of many-boson dynamics - Brouzos, Ioannis; Streltsov, Alexej Iwanowitsch; Negretti, Antonio; Said, Ressa S.; Caneva, Tommaso; Montangero, Simone; Calarco, Tommaso (Physical review. A, Atomic, molecular, and optical physics, 2015)
We apply the concept of quantum speed limit (QSL)—the minimal time needed to perform a driven evolution—to complex interacting many-body systems where the effects of interactions have to be taken into account. We introduce a general strategy to eliminate the detrimental effects of the interparticle repulsion and drive the system at the QSL by applying a compensating control pulse (CCP). To prove the principles we consider a prototypical many-body system, a bosonic Josephson junction, and investigate a transfer of atoms from the ground state of one well to the ground state of the neighboring well, at increasing levels of complexity—from a textbook two-level approximation to full many-body treatment. By tracing the efficiency of the CCP protocol we show that the driven dynamics does follow the geodetic pathway and, therefore, it is optimal. The CCP strategy, applicable for a general interacting quantum many-body system with strong driving, can be of a practical relevance for the experimental implementation of quantum technology protocols, as quantum simulations or matter-wave metrology.
Gesehen am 29.05.2020